2022
DOI: 10.56889/owua8196
|View full text |Cite
|
Sign up to set email alerts
|

Role of Governmental Regulatory Controlling Procedures Between Political Hazards and Risk Management

Abstract: Both domestic and international developers are inextricably exposed to political uncertainty and hazards for construction activities on a global scale, either deliberately or inadvertently. Effectively managing political hazards in the developmental sector is essential for project performance, achievement and success. In developmental projects, The Organization Control theory, upon which this research is anchored, applied quantitative methodology with a positivist paradigm using SmartPLS as a statistical tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In accordance with the obtained results of the research, the necessity of implementing such a model is observed, where the concrete example in the Republic of Serbia shows that the incomplete Central Register of planning documents leads to the formation of eSpace, as a comprehensive centralized system, through which the transparent and efficient preparation and distribution of digitized planning documents and electronic data. This research adds the additional role of the interaction effect of government regulatory control procedures between political hazards and risk management [53]. Also, it is necessary to improve the current state of planning documentation and legal regulations related to the use and construction of land.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the obtained results of the research, the necessity of implementing such a model is observed, where the concrete example in the Republic of Serbia shows that the incomplete Central Register of planning documents leads to the formation of eSpace, as a comprehensive centralized system, through which the transparent and efficient preparation and distribution of digitized planning documents and electronic data. This research adds the additional role of the interaction effect of government regulatory control procedures between political hazards and risk management [53]. Also, it is necessary to improve the current state of planning documentation and legal regulations related to the use and construction of land.…”
Section: Discussionmentioning
confidence: 99%